2022
DOI: 10.3390/ijerph192316004
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown: Impact on Oral Health-Related Behaviors and Practices of Portuguese and Spanish Children

Abstract: This study aimed to assess and compare the impact of COVID-19 pandemic lockdowns on the oral health attitudes, dietary habits and access to dental care of Portuguese and Spanish children. A cross-sectional observational study involving caregivers of 3–17-year-old children who had cohabited during a COVID-19 pandemic lockdown in Spain and Portugal was conducted. Caregivers completed an online anonymous questionnaire. Aiming groups comparison, chi-square test was used for qualitative variables. 770 surveys were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
4
3
1
Order By: Relevance
“…Findings indicated that a substantial proportion of patients-81%-persisted in their usual tooth-brushing routine, a statistic that contrasts with the findings of Keles et al (32), who reported no change in brushing habits among 71% of their subjects. The research highlighted that the majority of participants did not incorporate flossing into their oral care regimen, corroborating the findings of Ana et al (33). Additionally, it was noted that a minor segment of the population, 18%, resorted to medicated toothpaste to maintain oral hygiene, possibly due to impediments in accessing dental services during the lockdown.…”
Section: Discussionsupporting
confidence: 78%
“…Findings indicated that a substantial proportion of patients-81%-persisted in their usual tooth-brushing routine, a statistic that contrasts with the findings of Keles et al (32), who reported no change in brushing habits among 71% of their subjects. The research highlighted that the majority of participants did not incorporate flossing into their oral care regimen, corroborating the findings of Ana et al (33). Additionally, it was noted that a minor segment of the population, 18%, resorted to medicated toothpaste to maintain oral hygiene, possibly due to impediments in accessing dental services during the lockdown.…”
Section: Discussionsupporting
confidence: 78%
“…Children with special healthcare needs require constant attention and assistance in facilitation of their routine oral healthcare practices irrespective of the pandemic, which could justify why 104 parents (68.0%) in our study reported that they noticed no change in their child's toothbrushing habits even during the pandemic. However, in contrast, it was observed that the pandemic had a detrimental impact on the daily toothbrushing habits of 6 to 11 years old Peruvian children which was linked to economic and emotional instability of these families that deprioritized non urgent practices like toothbrushing and 25.1% of the children evaluated by Gotler et al who revealed that lower frequency of toothbrushing was greater among older children who brush their own teeth and speculated that it was an impact of alteration in daily routine (2022) Other studies found that 22.9% and 21.9% of children decreased their frequency of toothbrushing , 16 parents (10.5%) reported an increase in their toothbrushing frequency which was also observed by Costa et al (2022) that revealed that 12.9% of Spanish children and 14.3% of Portuguese children of caregivers with higher level of education increased the frequency of toothbrushing during the lockdown when compared to the previous period. Mothers statistically signi cantly (p < 0.01) responded with observing no change in assisting their child in toothbrushing during the pandemic.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, other studies have noted an increase in dental caries following the lockdown. This increase could be associated with increased consumption of sugary and carbonated drinks during the pandemic, coupled with a decrease in the frequency and quality of oral hygiene [25,33].…”
Section: Discussionmentioning
confidence: 99%